A Toolchain for the Development of Agent-Based Smart Grid Control Solutions. Issue 2 (2020) - Törsleff, Sebastian; Derksen, Christian; Ludwig, Marcel; Linnenberg, Tobias; Wassermann, Erik; Loose, Nils; Fay, Alexander
Abstract: The energy transition necessitates a variety of control solutions to integrate renewables-based energy generation and unlock demand-side flexibility. To contribute to solving this challenge, the authors built a toolchain for developing smart grid control solutions. This toolchain consists of methodological, conceptual and technological components. In this contribution, we detail the way in which the toolchain facilitates the continuous utilization of control software artifacts across simulations, testbeds and deployment. This capability has the potential to significantly reduce engineering effort and build trust in agent-based control solutions for smart grids.